Analisis Resiprositas dalam Bergesernya Fungsi Kelembagaan Pokadulu dalam Kegiatan Pertanian Palawija di Kelurahan Waumere Kecamatan Tiworo Kepulauan Kabupaten Muna Barat - Haerul, Muhamad; Nalefo, La; Wianti, Nur Isiyana (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This study aims to describe the functions of Pokadulu institutions in agricultural activities in Waumere Sub-District, Tiworo Islands. This research was conducted from April to June 2018at Waumere, Tiworo Islands, and West Muna Regency. This research is to find out the current forms of reciprocity transformation in Pokadulu in Waumere, Tiworo Islands, West Muna Regency. To strengthen the data obtained, the researcher uses qualitative research methods to determine facts in the field and use informants. Key informants were determined by using purposive techniques as many as 2 respondents who are young farmers and old farmers who are still carrying out Pokadulu activities and who had left Pokadulu's activities. Based on the results of the study, the Pokadulu institutional function in farming activities managed by the older generation of farmers is to reduce farming costs in almost the whole process of farming activities starting from planting preparation, land clearing, planting, crop maintenance, harvesting and post-harvest through goods exchange or barter. The exchange system is limited to the kinship boundary and one-sided. While the farming activities managed by the generation of young farmers are only at the stage of land acquisition with the same purpose, namely to reduce farming costs, for example reducing rental costs at the land clearing stage in Waumere, Tiworo Islands, West Muna Regency.